The leaf aqueous extract of Myrianthus arboreus P. Beauv. (Cecropiaceae) improved letrozole-induced polycystic ovarian syndrome associated conditions and infertility in female Wistar rats - Marie Alfrede Mvondo; Flavie Ingrid Mzemdem Tsoplfack; Charline Florence Awounfack; Dieudonné Njamen (BMC, 2020)
Abstract Background Myrianthus arboreus P. Beauv. (Cecropiaceae) is a medicinal plant used to treat female infertility. The aqueous extract of M. arboreus leaves was found to improve the fertility of healthy female Wistar rats. In the present study, we proposed evaluating the effects of such an extract on an animal model of infertility caused by polycystic ovary syndrome (PCOS), in order to bring scientific evidence to the curative action of this plant against female infertility. Methods Following a 21-day administration (gavage) of letrozole (1 mg/kg), animals with PCOS, indicated by overweight and an estrous cycle blocked in the diestrus phase, were co-treated with letrozole (1 mg/kg) and the aqueous extract of M. arboreus leaves at doses of 20, 110 and 200 mg/kg. The positive control received clomiphene citrate (1 mg/kg) and metformin (200 mg/kg). The negative control received distilled water. Each group of animals was made up of 10 female rats. Vaginal smear was examined 7 days before and during co-treatments. Co-treatments were orally administered for 30 consecutive days and 5 animals per group were sacrificed thereafter for biochemical and histological analyses. The 5 remaining animals in each group were crossbred with males of proven fertility for 5 consecutive days. The daily examination of vaginal smears allowed evaluating fertility index. Following parturition, gestation rate was calculated. Results The aqueous extract of M. arboreus leaves reversed letrozole effects by decreasing body weight, abdominal fat accumulation, and serum levels of LH and testosterone (p < 0.001). Ovarian dynamic was improved and the number of tertiary, Graafian follicles (p < 0.001) and corpus luteum increased while that of cystic (p < 0.001) and atretic follicles (p < 0.01) decreased. These effects were associated with increased serum levels of estradiol, decreased ovarian oxidative stress, the resumption of the estrous cycle, the hypertrophy of uterine epithelial cells and increased fertility index and gestation rate. Conclusions These results justify at least in part, the traditional use of M. arboreus against female infertility and suggest that this plant could be a promising alternative treatment to improve symptoms associated with different PCOS phenotypes.